Policy Implementation Obligation to Use Environmentally Friendly Shopping Bags in DKI Jakarta - Hilda Rifani; Muh. Ilham; Rizki Amalia (Sean Institute, 2025)
The volume of waste from the people of Jakarta reaches 7,500 tons every day, 14% or 1,000 tons are single-use plastic waste. It is estimated that every day there are 650-800 thousand pieces of plastic bags entering the Bantargebang TPST. What needs to be worried about the massive use of plastic shopping bags, plastic shopping bags made from plastic (polyolefin or polyvinyl chloride) can be a threat to humans and the earth, in this case plastic shopping bags take 10 to 20 years to decompose, even taking up to hundreds of years to decompose completely. This study uses a qualitative method with a descriptive approach using the policy implementation theory from Grindle (1980) with primary and secondary data sources. Data collection techniques are carried out through interviews, observations and documentation, data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study indicate that the implementation of the policy of mandatory use of environmentally friendly shopping bags in DKI Jakarta has been running well in the dimension of the policy context, but in the dimension of the content of the policy, namely the types of benefits that will be generated and resources that are still not optimal. Inhibiting factors for the implementation of the policy of mandatory use of environmentally friendly shopping bags in DKI Jakarta, namely: limited socialization and communication, resistance from business actors, less than optimal supervision, lack of interest from business actors in providing environmentally friendly shopping bags. Efforts made to overcome obstacles to the implementation of the policy of mandatory use of environmentally friendly shopping bags in DKI Jakarta, namely: socialization and public education, support and incentives for traders and business actors, strengthening regulations and supervision, and affordable shopping bag alternatives.